Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Motivasi Sebagai Variabel Intervening Studi Pada PT. Surya Tsabat Mandiri - Muhammad Bintang Pangestu; Suwarto; Fitriani (Jurnal Manajemen DIVERSIFIKASI, 2026)
The objective of this study is to find out whether there is an influence between the leadership style and the working environment on the performance of employees with Motivation as a variable intervening on PT. SURYA TSABAT MANDIRI. This research method uses a quantitative approach, saturated sampling technique, respondents of 60 employees. The results of the research showed that Leadership Style influences employee performance, Working Environment influences Employee Performance, Leadership style influences Motivation, work environment influences motivation, motivation influences employees performance, and Leadership and Working environment have no direct influence on Employees performance through Motivation.